Efficacy and safety of serial membrane sweeping to prevent post term pregnancy: a randomised study - Saichandran, Sabita; Arun, Arthy; Samal, Sunita; Palai, Pallavee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prolonged pregnancy is associated with increased perinatal mortality and morbidity. Elective induction of labor at 41 weeks gestation is practiced routinely to improve the outcome. Membrane sweeping is old and simple method to promote onset of labor. To improve the success rate of this method, multiple attempts of sweeping has been tried and found to be effective and safe. Our aim was to assess the safety and efficacy of serial membrane sweeping in prevention of post term pregnancies. Methods: Participants were randomly assigned to serial membrane sweeping every 48 hours starting from 40 weeks until the labour commencement or up to 41 weeks of gestation. There was no intervention up to 41weeks in the control group. Labor was induced in women of both the groups who continued pregnancy beyond 41 weeks. Outcome measures include spontaneous onset of labor, mode of delivery, need of oxytocin for augmentation and maternal and fetal complications. Results: Significant number of women had spontaneous onset of labor before 41 weeks (47/48) and delivered vaginally in contrast to control group (23/50). There is significantly less need of oxytocin in study group. The prevention remained consistent and not dependent on parity and bishop score. Significant number in control group had meconium stained liquor. No other maternal or fetal complications noted. Conclusions: Serial membrane sweeping is both safe and effective in the prevention of pregnancy beyond 41 weeks. Hence reduces the post term pregnancy, need for induction of labour and related risks in low pregnancies.